The reputation management in the digital environment: Twitter as a tool of reputational communication in the Peruvian universities - Atarama Rojas, Tomás (2015)
The use of twitter to purposes of external communication is widespread among institutions of higher education. The short messages and the free access to information have turned Twitter into the perfect channel to manage and control the reputational communication in the institutions. This research aims to describe the operation of the tool for purposes of external communication and, through analysis of the use made by Peruvian universities with more activity in these medium, details some principles that serve to promote the development of reputational communication in these educational institutions through the digital environment.